2014
DOI: 10.1016/j.cja.2014.02.015
|View full text |Cite
|
Sign up to set email alerts
|

A fuzzy PID-controlled SMA actuator for a two-DOF joint

Abstract: Shape memory alloy (SMA) actuator is a potential advanced component for servosystems of aerospace vehicles and aircraft. This paper presents a joint with two degrees of freedom (DOF) and a mobility range close to ±60°when driven by SMA triple wires. The fuzzy proportional-integral-derivative (PID)-controlled actuator drive was designed using antagonistic SMA triple wires, and the resistance feedback signal made a closed loop. Experiments showed that, with the driving responding frequency increasing, the overst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…The fuzzy proportional-integral-derivative-(PID-) controlled actuator drive was designed using antagonistic SMA triple wires. This research showed the investigation of the external interference to the system proved the controllable maximum output [16].…”
Section: Tendon-based Parallel Manipulator Applicationmentioning
confidence: 79%
See 1 more Smart Citation
“…The fuzzy proportional-integral-derivative-(PID-) controlled actuator drive was designed using antagonistic SMA triple wires. This research showed the investigation of the external interference to the system proved the controllable maximum output [16].…”
Section: Tendon-based Parallel Manipulator Applicationmentioning
confidence: 79%
“…Shape memory alloy (SMA) actuator is a potential advanced component for servo systems of aerospace vehicles and aircraft. SMA triple wires perform two degrees of freedom (DOFs) connected with a joint where the mobility range close to ±60 ∘ in the research [16]. The fuzzy proportional-integral-derivative-(PID-) controlled actuator drive was designed using antagonistic SMA triple wires.…”
Section: Tendon-based Parallel Manipulator Applicationmentioning
confidence: 99%
“…But the fuzzy is a nonlinear control and the controlled system output has a static error [11]. Then fuzzy PID control which combines the traditional PID and fuzzy control algorithms is a solution [11][12][13][14][15][16][17][18]. However, the typical fuzzy PID controllers are experimentally designed based on working conditions of the control systems and their dynamic responses [19].…”
Section: Introductionmentioning
confidence: 99%
“…There is no systematic method to design and examine the number of rules, input space partitions, and membership functions (MFs). Hence, the typical fuzzy PID controllers cannot adapt for a wide range of working environments with large variation of perturbations [18]. As a result, other control techniques such as robust control, intelligent theory, or estimation methods are needed to combine with the fuzzy PID to overcome this weakness [14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…values, can satisfy the performance index of control system [10]. But the contradiction between dynamic and static performance of these fixed parameters as well as the contradiction between the setpoint and disturbance rejection can not be taken into account the system controller.…”
Section: Figure 1 Principle Block Diagram Of Pid Control Systemmentioning
confidence: 99%